2004
DOI: 10.1002/bit.20090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethanol, acetate, and phenol on toluene degradation activity and todlux expression in Pseudomonas putida TOD102: evaluation of the metabolic flux dilution model

Abstract: The reporter strain Pseudomonas putida TOD102 (with a tod-lux fusion) was used in chemostat experiments with binary substrate mixtures to investigate the effect of potentially occurring cosubstrates on toluene degradation activity. Although toluene was simultaneously utilized with other cosubstrates, its metabolic flux (defined as the toluene utilization rate per cell) decreased with increasing influent concentrations of ethanol, acetate, or phenol. Three inhibitory mechanisms were considered to explain these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…Biodegradation of aromatics, such as benzene and toluene, is known to be negatively impacted by the presence of ethanol and other compounds (Ma et al 2013;Osterreicher-Cunha et al 2009). For example, enzymes involved in aromatic biodegradation could be repressed (catabolic repression) or feedback inhibition (metabolic flux dilution) could occur in the presence of other compounds such as acetate, ethanol, or phenol (Duetz et al 1994;Lovanh and Alvarez 2004;Lovanh et al 2002;Ma et al 2013). These compounds can be groundwater contaminants and/or products of anaerobic processes.…”
Section: Effects Of the Presence Of Biodiesel In The Anaerobic Degradmentioning
confidence: 99%
“…Biodegradation of aromatics, such as benzene and toluene, is known to be negatively impacted by the presence of ethanol and other compounds (Ma et al 2013;Osterreicher-Cunha et al 2009). For example, enzymes involved in aromatic biodegradation could be repressed (catabolic repression) or feedback inhibition (metabolic flux dilution) could occur in the presence of other compounds such as acetate, ethanol, or phenol (Duetz et al 1994;Lovanh and Alvarez 2004;Lovanh et al 2002;Ma et al 2013). These compounds can be groundwater contaminants and/or products of anaerobic processes.…”
Section: Effects Of the Presence Of Biodiesel In The Anaerobic Degradmentioning
confidence: 99%
“…For example, higher 42 proportions of toluene in various mixtures of toluene and ethanol result in higher toluene 43 biodegradation rates (Lovanh et al 2002). This phenomenon, termed metabolic flux dilution 44 (Lovanh & Alvarez, 2004), is a form of noncompetitive inhibition of the degradation of a target 45 substrate due to the metabolism of another (likely initiated by different enzymes). This 46 and BTEX plumes were used to assess the validity of the metabolic flux dilution model, and to 70 gain fundamental insight to recommend practical solutions to accelerate BTEX biodegradation 71 (e.g., add nitrate to increase the electron acceptor pool and stimulate faster degradation of 72 ethanol and other easily degradable substrates that hinder BTEX biodegradation).…”
mentioning
confidence: 99%
“…First-order decay constants (determined after the compound-specific onset of 198 biodegradation) are summarized in The metabolic flux dilution model predicts that specific removal rates should be dilution model (Lovanh and Alvarez, 2004;Madigan et al, 2000;Gomez et al, 2008) …”
mentioning
confidence: 99%
“…By adding glucose as a growth substrate in the bioluminescence assays, the mineralization of biodegradable inducers (e.g., toluene) is severely, if not totally, reduced, thus maintaining a relatively constant aqueous concentration of the test compound for the duration of the experiments. A recent study with Pseudomonas putida TOD102 showed that alternative carbon sources hindered the rate of toluene biodegradation due to a phenomenon known as metabolic flux dilution, a form of noncompetitive competition in which the utilization of a carbon source in a mixture is proportional to its relative availability (Lovanh and Alvarez, 2004). In the bioluminescence assays, the concentration of glucose was 110 times higher than that of toluene.…”
Section: Description Of Biosensormentioning
confidence: 99%